Assessment of the ecological state and health of oil-contaminated Luvic Phaeozems Albic, Gleyic Albeluvisols, and Greyic Phaeozems after remediation by biochar - Anna Ruseva; Tatiana Minnikova; Sergey Kolesnikov; Elizaveta Kushnareva; Maxim Desyatnikov; Rama Daoud (Universitas Sebelas Maret, 2025)
Oil pollution in soil endangers the health of the natural ecosystem on a larger scale. However, the application of biochar as an oil-contaminated soil rehabilitative amendment material is an ecologically friendly practice that supports soil ecological function. Thus, the research was carried out to evaluate ecological and environmental changes and the health condition of biochar-treated oil-polluted Luvic Phaeozems, Albic, Gleyic Albeluvisols, and Greyic Phaeozems Albic soils. A controlled laboratory experiment was set up for 30 days, during which the soils were artificially oil-contaminated at 5% of the soil weight and treated with biochar derived from birch at 10% of the soil weight. At the end of the experiment period, a range of physical, chemical, and biological properties indices were determined. The findings showed that the application of biochar raised the integral biological condition indicator by 77% in Gleyic Albeluvisols, 47% in Luvic Phaeozems Albic, and 18% in Greyic Phaeozems Albic relative to oil-contaminated untreated controls. Moreover, adding biochar resulted in petroleum hydrocarbon content reduction by 48%, 41%, and 33% in Gleyic Albeluvisols, Luvic Phaeozems Albic, and Greyic Phaeozems Albic soils, respectively. These results confirm the efficiency of biochar as an effective agent for the improvement of the oil-contaminated soil health.